A diode-pumped femtosecond Pr:YLF laser emitting at the near-infrared 915 nm. (July 2022) - Luo, Saiyu; Gu, Han; Geng, Xiang; Tang, Xiao; Sheng, Chuanxiang; Li, Li; Cai, Zhiping
Highlights: First demonstration of NIR femtosecond Pr solid-state laser of any type. Double-sided symmetric dispersion arrangement by introducing a triple set of GTIs. The Pr:YLF crystal is pumped by a single blue laser-diode. 915-nm ultrafast pulse of 451 fs width at a repetition rate of 85.5 MHz. This Pr laser has an average output power of 257 mW and a pulse energy of 3 nJ. Abstract: Femtosecond pulse generation from diode-pumped praseodymium (Pr) lasers in the near-infrared has been a long pursuit for the optics community. Utilizing the Pr:LiYF4 crystal in a novel dispersion arrangement scheme that includes a set of triple Gires-Tournois interferometer mirrors, mode-locked ultrashort pulses as short as 451 fs at 915 nm have been achieved when the crystal is directly pumped by a blue laser-diode. The pulse energy is 3 nJ and peak power is 7.2 kW at the repetition rate of 85.5 MHz. This is the first demonstration of diode-pumped Pr lasers arriving the femtosecond regime.